PENINGKATAN PENGETAHUAN PENDIDIKAN SEKSUAL MELALUI PENGGUNAAN VIDEO PEMBELAJARAN PADA ANAK TUNAGRAHITA DI SLB-C YPPLB MAKASSAR - Haerunnisa; Mustafa; Usman Bafadal (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Among children with intellectual disabilities at SLB-C YPPLB Makassar. The research questions formulated for this study are: 1) What is the level of knowledge regarding sex education among children with intellectual disabilities at SLB-C YPPLB Makassar?, 2) What is the level of knowledge regarding sex education among children with intellectual disabilities at SLB-C YPPLB Makassar after the use of instructional videos?, and 3) Is there an improvement in the knowledge of sex education among children with intellectual disabilities at SLB-C YPPLB Makassar through the use of instructional videos? The objectives of this research are to determine: 1) The knowledge of sex education among children with intellectual disabilities prior to the use of instructional videos, 2) The knowledge of sex education among children with intellectual disabilities after the use of instructional videos, and 3) The improvement in the knowledge of sex education among children with intellectual disabilities. The subject of this study was a seventh-grade female student with an intellectual disability. Data collection techniques utilized an initial test (pretest) and a final test (posttest). Based on the research data gathered from the subject at SLB-C YPPLB Makassar, the conclusions of this study are: 1) The knowledge of sex education among children with intellectual disabilities at SLB-C YPPLB Makassar prior to the use of instructional videos fell into the highly inadequate category; 2) The knowledge of sex education among children with intellectual disabilities at SLB-C YPPLB Makassar after the use of instructional videos fell into the adequate category; 3) There is an improvement in the knowledge of sex education among children with intellectual disabilities at SLB-C YPPLB Makassar following the use of instructional videos.